Pengaruh Manipulasi O2 Sensor terhadap Unjuk Kerja Mesin Scooter Matic 4T - Ridzal Saiful Zein; Wegie Ruslan (JURNAL CITRA WIDYA EDUKASI, 2019)
In the current technological advancements that have developed rapidly in the automotive industry, especially in motorcycle products where many users want the best performance on their vehicles. Where is the fact motorized motorists tend to want optimal engine power compared to fuel consumption and low exhaust emissions. This can be seen from the number of engine power enhancing products compared to exhaust emission reducing products and fuel saver. So one way to improve engine performance is to manipulate the O2 sensor voltage to change the air flow ratio (AFR) ratio. This study aims to determine the effect of manipulation of the O2 sensor output voltage on torque (T) and power (P). Tests carried out using a dynojet engine, in the testing phase using a manipulator that has 4 types, the large independent variable type consists of 0.5 Ohm, 1 Ohm, 1.5 Ohm and 2 Ohm. From the test results obtained show that by manipulating the output voltage of the O2 sensor using the O2 sensor manipulator can raise the machine's performance. The torque obtained in testing has increased by 53.8% in manipulator type 3, for power has increased by 33.3%.